The Macroeconomic Effects of Migration from the New European Union Member States to the United Kingdom - Iakova, Dora (IMF Working Papers; Working Paper ;, 2007)
The United Kingdom allowed workers from the ten new European Union member countries immediate access to its labor market after the accession in 2004. This paper uses a general equilibrium framework to explore the dynamic adjustment of the UK economy to the postaccession surge in immigration. Simulations show that immigration is likely to have positive effects on economic growth, capital accumulation, consumption, and the public finances.